Rootstock/scion compatibility effects on yield components in avocado cv. Hass in three locations in Colombia - Córdoba-Gaona, Oscar de Jesús; Hernández-Arredondo, Juan David; Loaiza-Ruíz, Ruby Alejandra; Barrera-Sánchez, Carlos Felipe; Cano-Gallego, Lucas Esteban (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2024)
This work aimed to evaluate the effects of stem morphological alterations resulting from grafting, defined as compatibility and incompatibility between the rootstock and scion, on fruit yield and quality of avocado cv. Hass in three producing areas in Colombia (Rionegro, El Peñol and Anserma) over two consecutive years. Avocado orchards were established by seedlings obtained by grafting Hass scions upon creole rootstock seedlings. Avocado grafted plants were propagated with tip grafting, with a scion bud of cv. Hass (standard procedure). A split-plot design with a blocking factor per locality was used. Main plot corresponded to the harvest season, and subplots to rootstock/scion degree of compatibility. Results showed that compatibility treatments did not significantly affect yield (kg/tree) and fruit number per tree. In 2020, main harvest presented the highest yield (48.05 kg/tree) and fruit number (321 fruits/tree), while in 2021, secondary harvest presented the lowest yield (7.31 kg/tree) and the fruit number (52 fruits/tree). Main harvests contributed with 71.4% for total average production of each year, while secondary harvests completed the fruit yield with 28.6%. Finally, rootstock/scion compatibility did not affect fruit number, fruit caliber distribution, and yield per tree, while yield was affected solely by harvest season.